THE ROLE OF ENERGY COMPANIES IN ACHIEVE NET ZERO EMISSIONS IN INDONESIA BASED ON SUSTAINABILITY DISCLOSURES PERIOD 2020 – 2022 - Siswanti, Tutik; Wijayanti, Dian (Feb Universitas Dirgantara Marsekal Suryadarma, 2025)
This study aims to analyze the contribution of energy companies listed on the IDX in efforts to achieve zero carbon emissions through disclosure of sustainable reports. The object of this study is energy companies listed on the IDX for the period 2020-2022. The research sample was determined based on purposive sampling. The data used were financial reports and sustainability reports published on the IDX and the company's website. The total data was 195 financial reports and sustainability reports from 65 companies for 3 years. The data analysis method in this study is content analysis and statistical analysis. Sustainability disclosure is measured based on 6 indicators; climate change, greenhouse gas emission accounting, energy consumption accounting, efficiency and cost of greenhouse gas reduction, carbon emission accounting, and greenhouse gas prevention efforts. Content analysis is carried out by providing a dummy measurement scale from 0 - 6, based on the description of sustainability disclosure. The results of the study found that in general, sustainable disclosure from 2020 - 2022 increased, but was still low, as indicated by an average score of 1-2. This shows that most companies disclose qualitatively and quantitative data, but have not disclosed progress on the form of tables or graphs, as well as strategies and efforts to prevent carbon emissions from their business activities in the future.Companies are increasingly compliant in sustainability disclosures as indicated by an increase in the quality of disclosures in sustainability reports, although it has not yet reached a maximum score of 6. Based on the difference test, it was found that there was a difference in the quality of disclosures from year to year (2020-2021): CC, EC, RC, and (2021-2022): CC, CHG, EC, RC. Meanwhile, it was also found that there was no difference in the quality of disclosures (2020-2021): CHG, ACC, MTG), and (2021-2022): ACC, MTG.Keywords: Sustainability, Carbon Emissions, Energy, Compliance